Stability Analysis of Partially Submerged Landslide with the Consideration of the Relationship between Porewater Pressure and Seepage Force - Yang Wang; Le Yu; Tianci Yin; Lanbing Yu; Zhitao Huo (Geofluids)
For partially submerged landslides, hydrostatic and hydrodynamic pressures, related to water level fluctuation and rainfall, are usually expressed in the form of porewater pressure, seepage force, and buoyancy. There are some connections among them, but it is very easy to confuse one force with another. This paper presents a modified mathematical expression for stability analysis of partially submerged landslide and builds the relationship between porewater pressures and buoyancy acting on the underwater zone of partially submerged landslide and the relationship among porewater pressures, seepage force, and buoyancy acting on partially submerged zone. The porewater pressures acting on the underwater slice are calculated using hydrostatic forces, and the porewater pressures acting on the partially submerged slice are estimated by an approximation of equipotential lines and flow lines under the steady state seepage condition. The resultant of the porewater pressures acting on the underwater slice equals the buoyancy, and that acting on the partially submerged slice is equivalent to the vector sum of seepage force and the buoyancy. The result shows there are two equivalent approaches for considering the effect of water on landslide stability in the limit equilibrium method. One is based on total unit weight and porewater pressures, and the other is in terms of the buoyant weight and the seepage force. The study provides a modified model for simplifying the complex boundary porewater pressures in limit equilibrium analysis for the stability of the partially submerged landslide.